Determination of bioactive compounds, antimicrobial activity, and the phytochemistry of the organic banana peel in Thailand - Naksing, Thanyarat (2021)
Banana fruit is enriched with phytonutrients, minerals, and its peel, which is mostly discarded as waste. This research aimed to study its bioactive compound properties, antimicrobial activity, and identify and characterize the constituents of organic banana peel extract (BPE), composed of six species (i.e., Kluai Homthong, Kluai Namwa, Kluai Kai, Kluai Hukmook, Kluai Lebmuernang, and Kluai Homtaiwan). Total phenolic content (TPC), antioxidant content, and ferric-reducing antioxidant power (FRAP) were important in BPE of Kluai Kai. BPE of Kluai Hukmook could inhibit Aeromonas hydrophila and Staphylococcus aureus. The Fourier-transform infrared spectroscopy (FTIR) spectrum exposed diverse compounds of primary and secondary phytochemicals. Four main constituents, including acetic acid, formic acid, 1,2-benzenediol,3-methyl-, and 4-hydroxy-2-methylacetophone derived from gas chromatography-mass spectroscopy (GC-MS), demonstrated their antioxidant properties and antimicrobial activity. This result suggests that organic banana peel can both be applied as an antioxidant and antimicrobial substance. BPE increases the value of banana peels (BPs) and reduces the burden of its waste disposal in the environment.